Sodium Butyrate Alleviates Intestinal Inflammation in Mice with Necrotizing Enterocolitis - Qian Sun; Yan-Chun Ji; Zheng-Li Wang; Xiang She; Yu He; Qing Ai; Lu-Quan Li (Mediators of Inflammation)
Objective. To determine the role of sodium butyrate in intestinal inflammation via regulation of high-mobility group box-1 (HMGB1), we analyzed the potential mechanism in necrotizing enterocolitis (NEC) in a neonatal mouse model. Methods. A NEC model was created with hypoxia and cold exposure and artificial overfeeding. C57BL/6 neonatal mice were randomized into three groups: the control, untreated NEC, and sodium butyrate (150 mM)-pretreated NEC groups. Pathological variations in ileocecal intestinal tissue were observed by HE staining and scored in a double-blind manner. The mRNA expression levels of HMGB1, Toll-like receptor 4 (TLR4), nuclear factor-κB (NF-κB), and inflammatory cytokines in intestinal tissues were determined by quantitative real-time PCR. The protein levels of HMGB1 and associated cytokines in intestinal tissues were evaluated using ELISA. The relative protein expression levels of TLR4 and NF-κB in intestinal tissues were quantified by western blot. Results. Sodium butyrate administration improved the body weight and survival rate of NEC mice; relieved intestinal pathological injury; reduced the intestinal expression of HMGB1, TLR4, NF-κB, interleukin- (IL-) 1β, IL-6, IL-8, and TNF-α; and increased the intestinal expression of IL-10 (P<0.05). Treatment with butyrate decreased the proportion of opportunistic Clostridium_sensu_stricto_1 and Enterococcus and increased the proportion of beneficial Firmicutes and Lactobacillus in the NEC model. Conclusions. Sodium butyrate intervention relieves intestinal inflammation and partially corrects the disrupted intestinal flora in mice with NEC.